Effectiveness of Balance Scorecard in Determining The Company's Business Strategy - Nofiyanti, Nofiyanti; Winanti, Winanti; Asbari, Masduki; Fajrin, Andira; Muhammad Rizal, Imam; Nafis Ayyasy, Ahmad; Sefthian, Sefthian (Journal of E-business and Management Science, 2024)
One of the tools to measure the performance of the company's business development performance is the Balance Scorecard. The function of the Balance Scorecard is to review the company's business performance and is used as information in the form of reports that can be presented in the form of financials in a certain period. Another important role is as a tool to help develop future business strategies using work efficiency. With this approach, it is hoped that the organization can develop with an integrated and more comprehensive plan, this allows the organization to adapt when there are changes in the business environment and it is easier to achieve strategic and effective goals... An understanding of performance is a description of the level of achievement of a policy program or activity in the process of realizing the company's goals, vision and mission as outlined in the company's strategic planning. Meanwhile, company performance is a complete state of affairs regarding the company in a certain period and becomes a result or achievement that affects the company's operational activities on the utilization of its human resources. The author in this case presents information about understanding the balance scorecard both in terms of functional, how to use, examples of balance score card implementation to determine the company's effective and efficient business strategy for the sustainability of the company. The method used by the author is to take descriptive qualitative data by collecting data through literature review studies of several journals, articles from websites in the form of discussions about functions, steps that must be taken, balance scorecard perspectives and balance scorecard implementation.